Assessment and Examination of Female Rape Victims and Their Genital Injuries (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The prevalence of genital injury resulting from sexual assault has been an area of interest to the scientific and health care community. The present study was conducted to assess female rape victims and their genital injuries. Materials & methods: The present retrospective study was conducted in the department of Gynaecology. It consisted of 28 female patients of rape victims. All suspected victims were examined in gynecology and forensic medicine department. A through vaginal examination was performed by gynecologist. Results: Age group 20-25 years had 16 females and age group 25-30 years had 7 females and 30-35 years had 5 females. The difference was significant (P< 0.05). Tanner staging- hair stage II was seen in 8, hair stage III in 20, V- shaped notches were single in 4, multiple in 24. Notches were at 6 o clock position in 5, 9 o clock position in 6 and at both positions in 17. The difference was significant (P< 0.05). Conclusion: The number of rapes is increasing day by day. A through gynecological examination is required to confirm the crime.